2016
DOI: 10.1093/nar/gkw863
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule FRET studies of the cooperative and non-cooperative binding kinetics of the bacteriophage T4 single-stranded DNA binding protein (gp32) to ssDNA lattices at replication fork junctions

Abstract: Gene 32 protein (gp32) is the single-stranded (ss) DNA binding protein of the bacteriophage T4. It binds transiently and cooperatively to ssDNA sequences exposed during the DNA replication process and regulates the interactions of the other sub-assemblies of the replication complex during the replication cycle. We here use single-molecule FRET techniques to build on previous thermodynamic studies of gp32 binding to initiate studies of the dynamics of the isolated and cooperative binding of gp32 molecules withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…The template strand contains a 15-nt poly(deoxythymidine) [p(dT) 15 ] sequence that can form an association complex with up to two cooperatively bound gp32 protein monomers at one time. Recently, Lee et al (15) showed that smFRET signals observed from this same p/t DNA construct in the presence of gp32 undergo intermittent protein-induced fluctuations, which reflect changes in the end to end distance of the ssDNA template caused by binding and dissociation of gp32 proteins.…”
Section: Significancementioning
confidence: 98%
“…The template strand contains a 15-nt poly(deoxythymidine) [p(dT) 15 ] sequence that can form an association complex with up to two cooperatively bound gp32 protein monomers at one time. Recently, Lee et al (15) showed that smFRET signals observed from this same p/t DNA construct in the presence of gp32 undergo intermittent protein-induced fluctuations, which reflect changes in the end to end distance of the ssDNA template caused by binding and dissociation of gp32 proteins.…”
Section: Significancementioning
confidence: 98%
“…As indicated above, we illustrate our approach using the macromolecular system studied by Lee et al , 8 in which a ssDNA template interacts with the T4 bacteriophage gp32 binding protein (see Fig. 1A).…”
Section: Conformational Transition Pathways and The Role Of Intermentioning
confidence: 99%
“…Experimentally, this requires making measurements at a higher time resolution than that used in the Lee et al study. 8 As the time resolution of a single-molecule fluorescence measurement approaches a few milliseconds, the signal will necessarily become too noisy to extract the state of the system through direct visualization of single-molecule trajectory data (e.g., by HMM analysis). Rather, we show below how equivalent information may be obtained through the application of the generalized concepts of TCFs.…”
Section: Conformational Transition Pathways and The Role Of Intermentioning
confidence: 99%
See 2 more Smart Citations